Environmental Effects on the Expression of Genotypic Differences in Wheat Grain Viscosity. Issue 3 (1st May 2015) - Levy Häner, Lilia; Stamp, Peter; Kreuzer, Michael; Herrera, Juan Manuel; Pellet, Didier
ABSTRACT: Wheat ( Triticum aestivum L.) grains are widely used as a feed. Contrasting to the demand of a high viscosity for bread making, a low viscosity is required for monogastric livestock. The impact of genotype and climate on this trait is largely unknown. Therefore, seven wheat varieties grown at five sites in Switzerland from 2007 to 2009 were analyzed for the potential applied viscosity, that is, the viscosity after inactivation of the plants' own enzymes. The varieties covered a wide range in viscosity, thus representing different classes of wheat quality. Agronomical traits and meteorological data were related to viscosity by correlation and regression analyses. The average daily temperature (ADT) from 20 to 34 d after heading was closely and negatively correlated with viscosity ( r = −0.73), which, on the average over all varieties, explained 54% of the variability in viscosity. The impact of precipitation was just 4%. One variety was temperature insensitive. In the six thermosensitive varieties, the viscosity in a given environment could be predicted accurately by a linear regression developed from the average temperature during grain development. The existing genetic variability enables the identification of high‐quality feed wheat varieties and facilitates breeding for temperature‐stable, low‐viscosity feed wheat varieties.